2001
DOI: 10.1016/s0008-6363(01)00427-8
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced postprandial lipemia impairs endothelium-dependent dilation of the brachial artery in men

Abstract: We conclude that pronounced postprandial lipemia is associated with transient impairment of endothelial function. Our findings support the notion that impaired triglyceride metabolic capacity plays an important role in atherogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
76
5
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 44 publications
14
76
5
3
Order By: Relevance
“…In contrast to previous studies showing impaired endothelial function after high-fat meals containing olive oil [14] or saturated fat [23,[32][33][34], FMD was not impaired 4 h after a high-fat meal containing predominantly unsaturated fatty acids. In fact, when the sample as a whole was considered, FMD significantly increased at 4 h. However, fasting triacylglycerols status, triacylglycerols response to the meals, and the fatty acid profile of the meals were important determinants of the direction and magnitude of postprandial responses.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous studies showing impaired endothelial function after high-fat meals containing olive oil [14] or saturated fat [23,[32][33][34], FMD was not impaired 4 h after a high-fat meal containing predominantly unsaturated fatty acids. In fact, when the sample as a whole was considered, FMD significantly increased at 4 h. However, fasting triacylglycerols status, triacylglycerols response to the meals, and the fatty acid profile of the meals were important determinants of the direction and magnitude of postprandial responses.…”
Section: Discussioncontrasting
confidence: 99%
“…Another study [43] proposed that the apparent reduction in FMD after a meal high in saturated fat is actually the result of peripheral vasodilation (measured as an increase in basal artery diameter), rather than a change in endothelial function in itself, and this pattern was confirmed in some [44][45][46] but not all [23,33,47] recent studies. In the present study, neither baseline artery diameter nor peak artery diameter were significantly changed after high-fat meals that are rich in unsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 93%
“…We and others have shown that pronounced postprandial lipaemia represents a risk factor for the development of coronary artery disease [2,3] and elicits potential atherogenic effects including endothelial dysfunction [4] and increased blood coagulability [5].…”
Section: Introductionmentioning
confidence: 96%
“…There is now a large body of evidence indicating that a single session of moderate exercise can reduce subsequent postprandial lipemia by ~20-25% (7). Thus, given the reported relationship between postprandial lipemia and endothelial dysfunction (4,5), we hypothesized that exercise of this nature could attenuate the postprandial decrement in endothelial function.…”
mentioning
confidence: 99%
“…It is now evident that systemic inflammation is increased (2,3) and that endothelial function is impaired (4,5) postprandially, with some studies reporting that the postprandial decrement in endothelial function is proportional to the postprandial triglyceride rise (4,5). As endothelial dysfunction and inflammation are central to atherogenic progression (6), it is likely that these transient postprandial changes, repeated on a daily basis, have implications for long-term risk of vascular disease.…”
mentioning
confidence: 99%